OPTIMIZATION OF PERFORMANCE OF BHABINKAMTIBMAS POLRES SRAGEN THROUGH COUNSELING AND COUNSELING IN PREVENTION OF THE CRIMINAL ACTION OF THE WEIGHTING THEFT - Patuan Sihombing (Indonesian Journal of Police Studies, 2022)
ABSTRACT OPTIMIZATION OF PERFORMANCE OF BHABINKAMTIBMAS POLRES SRAGEN THROUGH COUNSELING AND COUNSELING IN PREVENTION OF THE CRIMINAL ACTION OF THE WEIGHTING THEFT PATUAN SAUR ANDRE JERIKO SIHOMBING, 18,059, patuansihombing29@gmail.com Maintenance of security and public order (harkamtibmas) as a form of one of the main tasks of the National Police. It is difficult to realize Harkamtibmas during the Covid-19 pandemic because many people have lost their jobs. Such conditions trigger the emergence of public intentions to commit crimes. Various ways that the community does include acts that violate existing laws and regulations. One of the acts that violate the law is committing the crime of theft by weight. To reduce the crime rate, a pre-emptive effort from the Police is needed in the form of coaching and counseling activities carried out by Bhabinkamtibmas in order to prevent criminal acts of theft by weighting in the context of creating harkamtibmas. This research was conducted to find out the implementation of guidance and counseling activities by Bhabinkamtibmas at Polres Sragen, the factors that influence it and how to improve the performance of Bhabinkamtibmas in preventing the crime of theft by weighting in order to create harkamtibmas at Polres Sragen. In carrying out the research, the author uses qualitative methods with primary and secondary data collection techniques taken from the results of structured interviews with predetermined sources. In this final project, the author uses several concepts and theories that are used as analytical tools in discussing each of the problems that have been determined. The concepts and theories used are the concept of coaching and counseling, the concept of Bhabinkamtibmas, management theory (SDO), and communication theory. The results show that the coaching and counseling activities carried out by Bhabinkamtibmas at the Sragen Police Station are not optimal so that the crime of theft with weighting has increased. The less than optimal activities carried out by Bhabinkamtibmas are caused by several factors, which consist of internal factors and external factors. So the researchers suggest that the personnel comply more with the attention that has been given regarding the picket duties so that Bhabinkamtibmas can be maximized in its performance.